The TAM receptor Tyro3 regulates myelination in the central nervous system. Issue 4 (1st February 2017) - Akkermann, Rainer; Aprico, Andrea; Perera, Ashwyn A.; Bujalka, Helena; Cole, Alistair E.; Xiao, Junhua; Field, Judith; Kilpatrick, Trevor J.; Binder, Michele D.
Abstract : Myelin is an essential component of the mammalian nervous system, facilitating rapid conduction of electrical impulses by axons, as well as providing trophic support to neurons. Within the central nervous system, the oligodendrocyte is the specialized neural cell responsible for producing myelin by a process that is thought to be regulated by both activity dependent and independent mechanisms but in incompletely understood ways. We have previously identified that the protein Gas6, a ligand for a family of tyrosine kinase receptors known as the TAM (Tyro3, Axl, and Mertk) receptors, directly increases oligodendrocyte induced myelination in vitro . Gas6 can bind to and activate all three TAM receptors, but the high level of expression of Tyro3 on oligodendrocytes makes this receptor the principal candidate for transducing the pro‐myelinating effect of Gas6. In this study, we establish that in the absence of Tyro3, the pro‐myelinating effect of Gas6 is lost, that developmental myelination is delayed and that the myelin produced is thinner than normal. We show that this effect is specific to the myelination process and not due to changes in the proliferation or differentiation of oligodendrocyte precursor cells. We have further demonstrated that the reduction in myelination is due to the loss of Tyro3 on oligodendrocytes, and this effect may be mediated by activation of Erk1. Collectively, our findings indicate the critical importance of Tyro3 in potentiating central nervous system myelination. GLIA 2017 GLIA 2017;65:581–591 Main Points: Loss of Tyro3 results in delayed developmental myelination and altered myelin wrapping. In vitro experiments suggest a direct effect of Tyro3 on oligodendrocyte myelination. The Erk1/2 pathway is implicated in this Tyro3 mediated effect.